PENERAPAN PEMBELAJARAN SOCIAL EMOTIONAL LEARNING DALAM PENGEMBANGAN KARAKTER EMPATI SISWA - Bella Silvia; H. Mislan; Ahmad Sayuti Nainggolan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the importance of developing empathy in elementary school students as part of character building. However, in learning practices, students are still found to lack caring, cooperation, and mutual respect. Therefore, the implementation of social emotional learning (SEL) is needed. This study aims to describe the application of social emotional learning in developing students' empathy character, describe the development of students' empathy after the implementation of the learning, and describe the supporting and inhibiting factors in its implementation in grade V of SD Islam Nurul Wahid, Jambi City. This study uses a qualitative approach with a case study design. The informants of this study consisted of the principal and grade V teachers, while students were used as objects of observation. Data collection techniques were carried out through observation, interviews, and documentation. The data obtained were then analyzed through the stages of data reduction, data presentation, and explanation of conclusions. The results of the study indicate that the implementation of social emotional learning is carried out in an integrated manner in learning activities through the habituation of positive attitudes, teacher role models, group discussions and religious activities at school. The implementation of this strategy has shown a positive impact on the development of student empathy, as seen in increased attitudes of helping each other, cooperation, mutual respect, and the ability to control emotions. Supporting factors for the implementation of this strategy include the active role of teachers, a conducive school environment, and consistent habits, while inhibiting factors include differences in student character, limited time, and lack of parental involvement.